2023
DOI: 10.1186/s12912-023-01516-1
|View full text |Cite
|
Sign up to set email alerts
|

The role of bidirectional associations between depression, anxiety, and emotional exhaustion on turnover intention among nurses: a multicenter cross-sectional study in China

Ning Qin,
Ziqiang Yao,
Meiying Guo

Abstract: Background A high turnover rate in nursing has become a global concern. Mental health issues may increase the turnover intention of nurses and lead to turnover behaviors. However, very little is known about the role of bidirectional associations between emotional exhaustion and depression/anxiety on turnover intention. This study aimed to examine the associations among depression, anxiety, emotional exhaustion and turnover intention, and to test the role of bidirectional associations between de… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(1 citation statement)
references
References 56 publications
0
1
0
Order By: Relevance
“…This constant exposure can have adverse effects on their mental health, potentially leading to burnout (Jennings, 2008; Kesarwani et al , 2020). The toll of witnessing distressing scenarios and dealing with the demands of patient care can contribute to heightened stress, anxiety and even depression as has been observed in the preexisting literature (Kaushik et al , 2021; Gao et al , 2012; Qin et al , 2023). A study conducted on nursing students in Hong Kong found that factors such as financial challenges, sleep disturbances, absence of leisure activities and self-perceived poor mental health were noteworthy factors associated with depression, anxiety and stress experienced in the previous week (Cheung et al , 2016).…”
Section: Introductionmentioning
confidence: 99%
“…This constant exposure can have adverse effects on their mental health, potentially leading to burnout (Jennings, 2008; Kesarwani et al , 2020). The toll of witnessing distressing scenarios and dealing with the demands of patient care can contribute to heightened stress, anxiety and even depression as has been observed in the preexisting literature (Kaushik et al , 2021; Gao et al , 2012; Qin et al , 2023). A study conducted on nursing students in Hong Kong found that factors such as financial challenges, sleep disturbances, absence of leisure activities and self-perceived poor mental health were noteworthy factors associated with depression, anxiety and stress experienced in the previous week (Cheung et al , 2016).…”
Section: Introductionmentioning
confidence: 99%